Osteopathic manipulative treatment in gynecology and obstetrics: A systematic review. (June 2016) - Ruffini, Nuria; D'Alessandro, Giandomenico; Cardinali, Lucia; Frondaroli, Franco; Cerritelli, Francesco
Highlights: First systematic review embracing all body of evidence on the effect of OMT on gynaecologic and obstetric conditions. High heterogeneity among studies prevented conclusive results, although positive trends emerged from the single studies. Necessity of further and more accurate studies in order to obtain solid results. Abstract: Objective: The aim of the review was to evaluate the effects of the osteopathic manipulative treatment (OMT) on women with gynaecological and obstetric disorders. Materials and methods: An extensive search from inception to April 2014 was conducted on MEDLINE, Embase, the Cochrane library using MeSH and free terms. Clinical studies investigating the effect of OMT in gynaecologic and obstetric conditions were included as well as unpublished works. Reviews and personal contributions were excluded. Studies were screened for population, outcome, results and adverse effects by two independent reviewers using an ad-hoc data extraction form. The high heterogeneity of the studies led to a narrative review. Results: 24 studies were included (total sample = 1840), addressing back pain and low back functioning in pregnancy, pain and drug use during labor and delivery, infertility and subfertility, dysmenorrhea, symptoms of (peri)menopause and pelvic pain. Overall, OMT can be considered effective on pregnancy related back pain but uncertain in all other gynaecological and obstetrical conditions. Only three studies (12.5%) mentioned adverse events after OMT. Conclusions: Although positive effects were found, the heterogeneity of study designs, the low number of studies and the high risk of bias of included trials prevented any indication on the effect of osteopathic care. Further investigation with more pragmatic methodology, better and detailed description of interventions and systematic reporting of adverse events are recommended in order to obtain solid and generalizable results.